Olfactory processing in adults with autism spectrum disorders. Issue 1 (December 2016) - Wicker, Bruno; Monfardini, Elisabetta; Royet, Jean-Pierre
Abstract Background As evidenced in the DSM-V, autism spectrum disorders (ASD) are often characterized by atypical sensory behavior (hyper- or hypo-reactivity), but very few studies have evaluated olfactory abilities in individuals with ASD. Methods Fifteen adults with ASD and 15 typically developing participants underwent olfactory tests focused on superficial (suprathreshold detection task), perceptual (intensity and pleasantness judgment tasks), and semantic (identification task) odor processing. Results In terms of suprathreshold detection performance, decreased discrimination scores and increased bias scores were observed in the ASD group. Furthermore, the participants with ASD exhibited increased intensity judgment scores and impaired scores for pleasantness judgments of unpleasant odorants. Decreased identification performance was also observed in the participants with ASD compared with the typically developing participants. This decrease was partly attributed to a higher number of near misses (a category close to veridical labels) among the participants with ASD than was observed among the typically developing participants. Conclusions The changes in discrimination and bias scores were the result of a high number of false alarms among the participants with ASD, which suggests the adoption of a liberal attitude in their responses. Atypical intensity and pleasantness ratings were associated with hyperresponsiveness and flattened emotional reactions, respectively, which are typical of participants with ASD. The high number of near misses as non-veridical labels suggested that categorical processing is functional in individuals with ASD and could be explained by attention-deficit/hyperactivity disorder. These findings are discussed in terms of dysfunction of the olfactory system.